A STRATEGIC PROCESS DEVELOPMENT AND IN VITRO CYTOTOXICITY ANALYSIS OF PACLITAXEL-LOADED LIPOSOMES - BOSE, PREETA; KUMAR DE, PINTU; SAMAJDAR, GOURAV; DAS, DIBYA (International Journal of Applied Pharmaceutics, 2023)
Objective: Liposomes are the controlled-release dosage form that improves the therapeutic efficacy of the drugs, prolongs the duration of action, reduces dosage frequency, and improves patient compliance. Methods: The thin-film hydration method was used to prepare Paclitaxel liposomes. In this process, cholesterol and sodium deoxycholate were used for the formulation, while chloroform and methanol were used as diluents. Percentage (%) drug release study was carried out in phosphate buffer at pH 7.4 in USP apparatus II (Paddle type)Model no VDA-8D, Veego, Mumbai, India. Results: Paclitaxel liposomes of various batches showed a percentage yield ranging from 38 to 84%. It was observed that (Encapsulation efficiency)EE% of Batches B1 to B10 were 0,62.33,59.51,50.21,44.30,82.25,88.95,72.34,77.37 and 70.63 percentage, respectively. Data fitting to the Peppas, Higuchi, 1st-order, and zero-order models was used to examine the optimized liposome (B7) release kinetic mechanism. Data comparison was done using the correlation coefficient (R2). Zero-order had an observed correlation coefficient (R2) of 0.9988, which was greater than that for other models. Therefore, it was clear that the medication was released from the formulation after the zero-order release. Conclusion: The prepared liposomes were subjected to various evaluation parameters like SEM, zeta potential, particle size analysis, drug release study, etc. Data showed that an increased concentration of cholesterol increases the drug release from liposomes. Microscopic images of the B7 batch revealed that liposomes are spherical and have regular surfaces. Formulation B7 shows good results and can be considered an optimized batch that has been selected for further cell line studies. The statistical analysis was used to support the improved formulation.